2022
DOI: 10.3390/ijerph19063223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Impulsivity on Competitive Anxiety in Female Athletes: The Mediating Role of Mindfulness Trait

Abstract: It has been demonstrated that athletes in competitive sports suffer from high levels of competitive anxiety, especially in the case of females. In this sense, it is necessary to identify possible risk and protective factors of those athletes in this collective who suffer from this type of anxiety. However, few studies analyze the relationship between Physical Activity (PA) and anxiety, identifying the possible mediation effect of trait variables such as impulsivity and mindfulness in female athletes. Hence, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The NCAA found that approximately 85% of certified athletic trainers believe anxiety is a current issue among college student athletes (Goldman, 2022;Moore & Gummelt, 2019). Results of studies showed that female and younger athletes are at a greater risk of anxiety (Terres-Barcala et al, 2022), and higher levels of somatic anxiety are experienced by females and cognitive anxiety in males (Hernandez et al, 2020). Anxiety can negatively impact athlete's self-confidence, performance abilities, lead to burnout (Peterson, 2019;Terres-Barcala et al, 2022), increased risk of sport injury (Ford et al, 2017), and negative self-conscious and distraction from the present moment (Lyon & Plisco, 2020).…”
Section: Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…The NCAA found that approximately 85% of certified athletic trainers believe anxiety is a current issue among college student athletes (Goldman, 2022;Moore & Gummelt, 2019). Results of studies showed that female and younger athletes are at a greater risk of anxiety (Terres-Barcala et al, 2022), and higher levels of somatic anxiety are experienced by females and cognitive anxiety in males (Hernandez et al, 2020). Anxiety can negatively impact athlete's self-confidence, performance abilities, lead to burnout (Peterson, 2019;Terres-Barcala et al, 2022), increased risk of sport injury (Ford et al, 2017), and negative self-conscious and distraction from the present moment (Lyon & Plisco, 2020).…”
Section: Anxietymentioning
confidence: 99%
“…Results of studies showed that female and younger athletes are at a greater risk of anxiety (Terres-Barcala et al, 2022), and higher levels of somatic anxiety are experienced by females and cognitive anxiety in males (Hernandez et al, 2020). Anxiety can negatively impact athlete's self-confidence, performance abilities, lead to burnout (Peterson, 2019;Terres-Barcala et al, 2022), increased risk of sport injury (Ford et al, 2017), and negative self-conscious and distraction from the present moment (Lyon & Plisco, 2020). Anxiety can be detrimental to adolescents' overall wellbeing (biological, psychological, and sociological) and the high amount of pressure in athletic competitions can exacerbate anxiety symptoms.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obsessive passion is more like an uncontrollable impulse, compelling athletes to sacrifice their personal health and stubbornly persist in training tasks that may improve their sports performance abilities, even in the face of a clear risk of injury ( 39 42 ). Furthermore, when individuals frequently fall into anxiety and remain immersed in this negative state for a long period, it can provoke anger and accompany reckless and impulsive behaviors ( 43 ), and individuals with strong emotional impulsiveness are more likely to have high levels of anxiety internalization symptoms ( 44 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have demonstrated the efficacy of psychological interventions, including mindfulness, on emotional and behavioural regulation in sports [ 28 , 29 , 30 , 31 ], hence the relevance of teaching regulatory skills, especially to young athletes participating in competitions [ 11 , 32 , 33 ], as they are subjected to greater sporting pressures (e.g., the obligation to win or to prove themselves to be the best).…”
Section: Introductionmentioning
confidence: 99%